COMPLAINTS IN ITALIAN AS A SECOND LANGUAGE: A STUDY ON (SOCIO)PRAGMATIC STRATEGIES AND PROSODIC VARIATIONS (Italiano LinguaDue, 2025)
This study analyzes the production of complaint acts in both L2 Italian and native Italian. It focuses on examining the relationship between the prosodic indices used by Italian learners and native speakers during the production of complaints, as well as the (socio)pragmatic strategies employed to execute these acts. To this end, a sample of protests produced by Arabic-speaking and Spanish-speaking learners, as well as by a group of native speakers through oral role-plays, to analysis was analysed from both a socio-pragmatic and a phonetic perspective. The preliminary results indicate a diverse range of outcomes. The learners, although exhibiting some differences between the two groups, tend to utilise more direct strategies and fewer modifications, which at times results in a reduction in politeness, particularly in situations of greater social distance. The prosodic analysis, which was limited to the study of the directive speech acts present in the complaints, revealed the presence of narrow pitch ranges and shorter durations of nuclear vowels in learners. Furthermore, the orders produced by the learners exhibited a less prominent final falling of the intonation pattern, resulting in a more mitigated prosody than that observed in the native data. This study can contribute to a deeper understanding of the interlinguistic competencies of learners from more distant languages and cultures and serve as a valuable resource for teaching linguistic acts that are considered more complex due to their higher face-threatening nature. Atti di protesta in italiano come seconda lingua: uno studio sulle strategie (socio)pragmatiche e sulle variazioni prosodicheQuesto studio analizza la produzione degli atti di protesta in parlanti nativi e non nativi di italiano, con l’obiettivo di esaminare la relazione tra gli indici prosodici e le strategie  (socio)pragmatiche impiegati durante la realizzazione dell’atto linguistico. A tal fine, è stato sottoposto ad analisi un corpus, prodotto attraverso simulazioni orali, dalla duplice prospettiva socio-pragmatica e fonetica. I risultati preliminari evidenziano una varietà di esiti. Sebbene emergano differenze tra i due gruppi di apprendenti, essi tendono ad adottare strategie più dirette e a utilizzare meno mitigazioni, con una conseguente riduzione del grado di cortesia, specialmente in contesti caratterizzati da maggiore distanza sociale. L’analisi prosodica, limitata allo studio degli atti linguistici direttivi all'interno delle proteste, ha rilevato negli apprendenti un’escursione tonale più ristretta e una durata più breve delle vocali nucleari. Inoltre, gli ordini prodotti dagli apprendenti mostrano una discesa intonativa finale meno marcata, con una resa prosodica più attenuata rispetto ai dati osservati nei parlanti nativi. Questo studio contribuisce a una comprensione più approfondita delle competenze interlinguistiche degli apprendenti provenienti da lingue e culture linguisticamente e culturalmente distanti, e rappresenta una risorsa preziosa per l’insegnamento degli atti linguistici che, per la loro natura intrinsecamente minacciosa per l’immagine sociale, risultano essere caratterizzati da una maggiore complessità.